MOTIVASI PERJALANAN, CITRA DESTINASI, DAN e-WOM SERTA PENGARUHNYA TERHADAP NIAT BERKUNJUNG (STUDI PADA PENGUNJUNG WISATA WADUK GROBOGAN KABUPATEN BOJONEGORO) - NUR RUKMANA, TIYA; LESTARI ANDJARWATI, ANIK (Jurnal Ilmu Manajemen (JIM), 2020)
Before doing the tourist activity of the majority community have several factors of consideration include travel motivation, destination image, and e-WOM, they use before doing activities which will give rise to intention a visit to a tourist destination. This research aimed to analyze and discuss the influence of Travel Motivation, Destination Image, and (e-WOM) on Visit Intention. This is a causal research method with a quantitative approach. The sampling method uses judgmental with 200 respondents of potential visitors. The statistical analysis technique used is multiple linear regression with SPSS program. The results show that there is a significant effect of travel motivation in visit intention, destination image in visit intention, and e-WOM in visit intention. Keywords: destination image; e-WOM; travel motivation; visit intention.